Improving Students' Critical Thinking through Science, Technology, Engineering, and Mixed Mathematics Learning on Ecosystem Materials - Imelda Rohmawati, Nurdiana; Prastiwi, Muji Sri (Universitas Pahlawan Tuanku Tambusai, 2026)
Critical thinking skills are an important competency in the 21st century that still needs to be improved in biology learning, especially in ecosystem materials. This study aims to analyze the influence of the STEM-based Blended Learning model on the critical thinking skills of high school students on ecosystem materials. The study used a pre-experimental method with a one-group pretest-posttest design. The subjects of the study were 36 students of class X of SMA Negeri 1 Bangilan. The BL-STEM model is applied through offline and online learning with a STEM approach, including Science in the form of understanding ecosystem concepts, Technology using Virtual Lab digital simulations (ecology lab learner), Engineering challenges engineering ecosystem balance, and Mathematics through data collection, graph analysis, and population change tables. The results showed an increase in the average critical thinking skill of 15.75 points, from 74.78 in the pretest to 90.53 in the posttest, and the increase was statistically significant and the N-Gain was 0.66 in the medium category. This increase was supported by the implementation of BL-STEM learning which reached 99.5% according to the LKPD and a very positive student response of 94.4%. Critical thinking skills are measured based on six indicators, namely interpretation, analysis, inference, explanation, evaluation, and self-regulation. These indicators are measured through students' ability to interpret and analyze data from simulations, identify cause-and-effect relationships between ecosystem components, draw conclusions about population change, evaluate ecological factors, and reflect on the thought process in solving ecosystem problems. Thus, BL-STEM learning is effective in improving students' critical thinking skills in high school ecosystem materials.